CuCl2 and FeCl3 as a New and Efficient Catalyst for the Oxidative Coupling of Aryl amines into 1‚1′′′-Binaphthalene-2‚2′′′-diamines in the Ionic Liquid Media - Montazeri, Naser; Tavana, Mahdie; Yousefian, Soghra; Taj Firooz, Farzane (Asian Journal of Chemistry, 2011)
A practical synthesis of 1‚1'-binaphthalene-1‚1'-diamines (BINAM) from a-naphthylamine is described here. The facile purification procedure of the method makes it amenable to gram scale synthesis of 1‚1'-binaphthalene-1‚1'-diamines with fairly high optical purity and yield of product.